Pembudayaan profil pelajar mandiri di Panti Asuhan Yatim Putri Aisyah Kadipiro melalui pendampingan 3K (karakter, keilmuan dan konseling) - Wulandari, Murfiah Dewi; Novitasari, Meggy; Rahmawati, Fitri Puji; Hidayati, Yulia Maftuhah; Hikmat, Mauly Halwat; Maharsiwi, Dwi Moqsa; Roisma, Rossa; Puspitasari, Ratna Kusuma; Wulandari, Diana Rizki Avita; Indaryati, Oktavia Nur; Ahsanu, Rizkika; Kusumawardani, Wiratri Nurul Ayu (Penamas: Journal of Community Service, 2023)
Orphanages need good services in cultivating character and scientific competence and getting support from counseling staff to express themselves freely, independently, flexibly, progressively, and happily. Character strengthening, knowledge, and counseling are necessary for orphanages to produce a superior generation. This service aims to cultivate an independent student profile through 3K (character, knowledge, and counseling) at the Putri Aisyiyah II Kadipiro Orphanage, Surakarta. Methods for implementing services include mapping and collecting data on initial conditions for partners, outreach with partners, mentoring children, monitoring and evaluation, and preparing reports and publications. The results of this service include 1) increasing the learning outcomes of students, 2) minimizing cases of violations committed by orphanage children, and 3) knowing the psychological/mental condition of orphanage children through psychological testing and counseling activities. From this service, it is hoped that we can optimize the abilities and solve the problems of orphaned children by cultivating 3K with a scientific concept integrated with character, which is the foundation of an independent student profile.